Imam Zarkasyi’s Contribution to Indonesia’s Modern Waqf Education System - Samindjaya, Syahruddin Sumardi; Laallam, Abdelkader; Hudaefi, Fahmi Ali; Issa, Bechir Mahamat; Ouassaf, Saidi; Oussedik, Mohamed Imad (Journal of Islamic Thought and Civilization, 2024)
The current study aimed to explore Imam Zarkasyi’s efforts to modernize pesantren institutions (Islamic boarding schools) through waqf organizations. The study drew on scholarly publications including books and academic papers as well as primary sources about Imam Zarkasyi by utilizing a qualitative, descriptive, and explanatory research methodology. The findings revealed that Zarkasyi’s educational perspectives and personal experiences significantly influenced the modernization of the waqf-based educational system. Zarkasyi’s proposals to enhance the pondok system’s modernity were based on his thorough understanding of the country’s educational culture. In response to the Dutch colonial administration, private educational institutions were established in 1926. These institutions offered students, educators, and community members the chance to acquire essential life skills and values in a unique educational setting. To ensure the continuity of these institutions, Zarkasyi transformed them into publicly owned enterprises through waqf establishment in 1958. As a waqif, he allocated a substantial portion of his fortune to be shared collectively among his three brothers. Zarkasyi aimed to ensure the sustainability of this approach by incorporating waqf principles which include attitudes, abilities, and praiseworthy characteristics. His initiatives continue to serve as a pedagogical model for private schools in Indonesia. This success motivates others to emulate the waqf concept, thereby contributing to the restoration and development of Islamic civilization.